On holomorphic solutions of some boundary-value problems for second-order elliptic operator differential equations - Mirzoev, S. S.; Safarov, R. F. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
In the class of holomorphic vector functions, we determine conditions of the solvability of boundary-value problem for a class of second-order differential operator equations, which are given in terms of operator coefficients containing in the equation and in the boundary condition.